PERANAN RADIODIAGNOSTIK IMAGING DALAM DETEKSI DAN PENENTUAN STADIUM PENYAKIT KARSIONA SERVIKS UTERI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
Gynecological examination alone is not sufficient for diagnosing the stage of cervical cancer. Radiologic examination should be conducted to detect distant metastases. Intravenous pyelography, lymphangiography, chest x-ray, barium enema abdominal and pelvic, CT scan, ultrasonography of liver, bone isorop scan are necessary. Key Words 1 cancer of the cervix uteri, staging, gynecological examination, radiological imaging examination